History of Europe and the Middle East course companion - Habibi, Mariam; Jafari, Peyman; Jones-Nerzic, Richard; Keys, David; Smith, David (Oxford University Press, 2012)
Ensuring an exhaustive understanding of the modern nation state and cementing source evaluation skills, this course book is packed with primary sources from across the entire region, preparing learners for top achievement. Written with an IB Assessment Consultant and matched to the IB approach to learning, it supports exceptional performance